2021
DOI: 10.52627/ijeam.v3i2.129
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Academic Supervision of Islamic Religious Education During the Covid-19 Pandemic

Abstract: This study aims to analyze the implementation of academic supervision of Islamic Religious Education supervisors during the covid-19 pandemic at the Ogan Komering Ulu Selatan District Public Middle School. The approach used is descriptive qualitative—data collection through observation, interview, and documentation techniques. The data analysis technique is carried out circularly, starting from data reduction, data display, and conclusion drawing is a data analysis technique carried out. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The pandemic makes educational institutions and teachers rack their brains so that the learning process can continue to be fun and not a double burden for children and parents (Suhairi & Badrudin, 2021;Rahman & Subiyantoro, 2021). There are times when children fill their spare time by watching television, listening to the radio, playing the play station not because they are interested in these activities, but because there is nothing they can do other than that.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic makes educational institutions and teachers rack their brains so that the learning process can continue to be fun and not a double burden for children and parents (Suhairi & Badrudin, 2021;Rahman & Subiyantoro, 2021). There are times when children fill their spare time by watching television, listening to the radio, playing the play station not because they are interested in these activities, but because there is nothing they can do other than that.…”
Section: Introductionmentioning
confidence: 99%
“…Its main fields include economics, health, tourism, and education. Great concern for the emergence of this virus is due to several reasons, including the speed of transmission of the virus that attacks the immune system, which can cause death (Fahrika & Roy, 2020;Suhairi & Badrudin, 2021). During the COVID-19 outbreak, fundamental changes occurred in society (Adham & Mahmudah, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, supervision is positively and significantly related to teacher performance and attitudes. Suhairi & Badrudin (2021) reported that the application of academic supervision by supervisors during the Covid-19 pandemic was carried out both online and offline, using individual and group methodologies, according to their research. However, the supervision operations have not run as efficiently as possible due to several problems supervisors, and schools have encountered.…”
Section: Introductionmentioning
confidence: 99%